2020
DOI: 10.1039/d0tb00456a
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme assisted peptide self-assemblies trigger cell adhesion in high density oxime based host gels

Abstract: Studying the influence of hydrogel matrices on the self-assembly behavior of peptides and interaction with cells guides the future development of engineered biomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Besides the introduction of gelatin or collagen in the ink [ 16 ], one strategy is to graft different cell adhesive peptides to alginate [ 34 , 35 ]. Recently, Criado-Gonzalez and coworkers [ 36 ] showed that the incorporation of a self-assembled phosphorylated tri-peptide, Fmoc-FFY (Fmoc: 9-fluorenylmethoxycarbonyl; F: phenylalanine; Y: tyrosine), within the polyethylene glycol [ 37 ] or hyaluronic acid hydrogels allowed for the promotion of fibroblast cell adhesion [ 36 , 38 ]. Moreover, this peptide exhibited antibacterial and anti-inflammatory properties [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the introduction of gelatin or collagen in the ink [ 16 ], one strategy is to graft different cell adhesive peptides to alginate [ 34 , 35 ]. Recently, Criado-Gonzalez and coworkers [ 36 ] showed that the incorporation of a self-assembled phosphorylated tri-peptide, Fmoc-FFY (Fmoc: 9-fluorenylmethoxycarbonyl; F: phenylalanine; Y: tyrosine), within the polyethylene glycol [ 37 ] or hyaluronic acid hydrogels allowed for the promotion of fibroblast cell adhesion [ 36 , 38 ]. Moreover, this peptide exhibited antibacterial and anti-inflammatory properties [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we have investigated the tripeptide Fmoc-FF p Y as precursor and Fmoc-FFY as hydrogelator. This is a model system well studied by our group over the last years [ 8 , 11 , 16 , 17 , 18 ]. When Fmoc-FF p Y (5 mg/mL, 6.44 mM) is dissolved in buffer solution at room temperature (Borax buffer 25 mM, pH 9.5, 20 °C), the addition of AP (1 mg/mL, 6.67 µM) induces the self-assembly of Fmoc-FFY in β-sheet organization and then the supramolecular hydrogel is obtained in 20 min.…”
Section: Resultsmentioning
confidence: 99%
“…This opened the route to the precise localization of peptide self-assemblies, and a step that was taken in 2009 when Williams and Ulijn groups showed that peptide self-assembly can be initiated from covalently immobilized enzyme on a surface [ 10 ]. Our group further developed the localized enzyme-assisted self-assembly (LEASA approach by introducing seed-layers in addition to an enzyme-adsorbed layer to trigger the localized self-assembly growth [ 11 , 12 ], for catalytic and auto-catalytic self-assembled hydrogels [ 13 , 14 , 15 ] or self-assemblies initiated from nanoparticles surface [ 16 ] and in host materials [ 17 , 18 ]. This bottom-up approach is efficient in water and once the surface coated with an adequate enzyme, the localized self-assembled structure growth proceeds in an autonomous way [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of stimuli-responsive materials that can be employed as therapeutic agents attracts great attention in the biomedical field for drug delivery, 1,2 tissue engineering, 3,4 or biosensing applications. 5–7 These biomaterials aim to take advantage of biological stimuli like pH, 8 temperature, 9 enzyme activity, 10,11 or redox balance 5,12 to produce specific therapeutic effects. In this regard, reactive oxygen species (ROS), which is the term given to biologically relevant oxidants present in the human body as by-products of aerobic respiration, including hydrogen peroxide (H 2 O 2 ), the superoxide anion (O 2 ˙ − ), hydroxyl radical (˙OH), peroxynitrite (ONOO − ), single oxygen ( 1 O 2 ), and hypochlorite (OCl − ), has gained great importance in the last decade.…”
Section: Introductionmentioning
confidence: 99%